2022
DOI: 10.3390/su14084487
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Exercise, and Sports in Individuals with Skeletal Dysplasia: What Is Known about Their Benefits?

Abstract: There is a lack of knowledge about the practice of physical activity, exercise, and sports in people with skeletal dysplasia (SD). This study aimed to characterize the physical fitness of people with SD; investigate the benefits of physical activity, exercise, or sports programs for people with SD; identify the adapted physical activities that can be prescribed to individuals with SD; and identify the most common and effective structural characteristics and guidelines for the evaluation of individuals with SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Several characteristics emerged in the overall sample for this study on sway patterns. Having achondroplasia imposes challenges in the sensorimotor integration underlying balance regulation [ 33 , 43 ]. While the N group also incurred postural constraints from disproportionate limbs, the intervention effect inflicted further control difficulties, clearly highlighted by the LL group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several characteristics emerged in the overall sample for this study on sway patterns. Having achondroplasia imposes challenges in the sensorimotor integration underlying balance regulation [ 33 , 43 ]. While the N group also incurred postural constraints from disproportionate limbs, the intervention effect inflicted further control difficulties, clearly highlighted by the LL group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the general adult population have highlighted the existence of linear relations between physical activity, handgrip strength, body composition, and multimorbidity [ 29 ]. It has been reported that PwACH present poor physical fitness, low participation in physical activities and reduced energy expenditure compared with the general population [ 30 , 31 , 32 , 33 ]. While muscle size is a predetermining factor of muscle strength, PwACH present shorter stature, smaller muscle size and lower maximal voluntary contraction strength than average-height people [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, kyphosis posture can also interfere with physical appearance due to poor posture (Fauzie et al, 2023). Based on Juliana's research, 2015, a study of changes in posture in adolescence, the prevalence of kyphosis in adolescents was 79.7% (n = 47), of which 47.5% (n = 28) showed changes on the frontal side and 61% (n = 36) there is a change on the sagittal side (Jacinto et al, 2022). Kyphosis is a spinal deformity that occurs in adolescents.…”
Section: Introductionmentioning
confidence: 99%